Magnitude and associated factors of intraoperative cardiac complications among geriatric patients who undergo non-cardiac surgery at public hospitals in the southern region of Ethiopia: a multi-center cross-sectional study in 2022/2023 - Abdulmelik, Amina; Tila, Mebratu; Tekilu, Takele; Debalkie, Ashebir; Habtu, Elias; Sintayehu, Ashagrie; Dendir, Getahun; Gordie, Naol; Daniel, Abel; Suleiman Obsa, Mohammed (Frontiers in Medicine, 2024)
Background Intraoperative cardiac complications are a common cause of morbidity and mortality in non-cardiac surgery. The risk of these complications increased with the average age increasing from 65. In a resource-limited setting, including our study area, the magnitude and associated factors of intraoperative cardiac complications have not been adequately investigated. The aim of this study was to assess the magnitude and associated factors of intraoperative cardiac complications among geriatric patients undergoing non-cardiac surgery. Methods An institutional-based multi-center cross-sectional study was conducted on 304 geriatric patients at governmental hospitals in the southern region of Ethiopia, from 20 March 2022 to 25 August 2022. Data were collected by chart review and patient interviews. Epi Data version 4.6 and SPSS version 25 were used for analysis. The variables that had association (p < 0.25) were considered for multivariable logistic regression. A p value < 0.05 was considered significant for association. Result The overall prevalence of intraoperative cardiac complications was 24.3%. Preoperative ST-segment elevation adjusted odds ratio (AOR = 2.43, CI =2.06–3.67), history of hypertension (AOR = 3.42, CI =2.02–6.08), intraoperative hypoxia (AOR = 3.5, CI = 2.07–6.23), intraoperative hypotension (AOR = 6.2 9, CI =3.51–10.94), age > 85 years (AOR = 6.01, CI = 5.12–12.21), and anesthesia time > 3 h (AOR =2.27, CI = 2.0.2–18.25) were factors significantly associated with intraoperative cardiac complications. Conclusion The magnitude of intraoperative cardiac complications was high among geriatric patients who had undergone non-cardiac surgery. The independent risk factors of intraoperative cardiac complications for this population included age > 85, ST-segment elevation, perioperative hypertension (stage 3 with regular treatment), duration of anesthesia >3 h, intraoperative hypoxia, and intraoperative hypotension. Holistic preoperative evaluation, optimization optimal and perioperative care for preventing perioperative risk factors listed above, and knowing all possible risk factors are suggested to reduce the occurrence of complications.